Human capital from psychoanalytic perspective = Kapitał ludzki w ujęciu psychoanalitycznym - Barabasz, Adela (Zielona Góra: Faculty of Economics and Management Press)
The article is of theoretical nature. Its aim is to present the psychoanalytic understanding of the capital which is constituted by organisation members. It is them who decides about the effects of the operations of an organisation, both its successes and failures. This article attempts at describing the psychological mechanisms which determine the complex phenomenon called 'human capital' of an organisation.
Keywords: kapitał ludzki; psychoanaliza; hierarchia; human capital; psychoanalysis; hierarchy